Peppermint Leaf Extract Cream Increased Transforming Growth Factor β (TGF-β) Expression and Collagen Amount In The Male Wistar Rat's Skin Exposed to UVB - Made Ayu Mirah Wulandari; Anak Agung Gede Putra Wiraguna; Wimpie Pangkahila (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2023)
Peppermint leaves contain flavonoids, menthofuran, and other phenolic compounds that have antioxidant activity and are believed to inhibit collagen degradation in the skin. This study investigated the efficacy of a 5% peppermint leaf extract cream in increasing the transforming growth factor β (TGF-β) expression and collagen amount as indicators of collagen maintenance in male Wistar rats' skin exposed to UVB. Method A randomized post-test-only control group design was performed on male Wistar rats, local strains, aged 2-3 months, with body weights ranging from 180 to 200 grams. According to the sample calculation, 21 rats were randomly divided into three groups. The first group is the control group (without any treatment). The second group was treated with UVB without cream (UVB-only group), and the third group was treated with UVB + 5% peppermint leaf extract cream on exposed skin. After four weeks of treatment, the tissue samples were examined. The expression of TGF-β was evaluated by immunohistochemical examination, and the amount of collagen was examined by Picro-Sirius red staining. Comparative tests were performed on the measurement results of the three groups. The results showed a significant difference in the mean TGF-β expression and collagen amount among the three groups (p<0.001). The group exposed to UVB + 5% peppermint leaf extract cream had the highest mean TGF-β expression and collagen amount (77.41±5.79% and 82.57±2.18%, respectively), followed by the control group (63.17±12.22% and 74.05±7.15%) and the UVB-only group (50.54±11.10% and 65.65±5.56%). Administration of 5% peppermint leaf extract cream effectively increased TGF-β expression and collagen amount in the skin of male Wistar rats exposed to UVB compared to the control and the UVB-only groups.